Optimal planning and design of seawater RO brine outfalls under environmental uncertainty - Maalouf, Sami; Rosso, Diego; Yeh, William W.-G. (Desalination, 2014)
Increasing demand for water in urban areas and agricultural zones in arid and semi-arid coastal regions has urged planners and regulators to look for alternative renewable water sources. Seawater reverse osmosis desalination plants have become an essential supply source for the production of freshwater in such regions. However, disposal of hypersaline wastes from the plants in many of these regions has not been fully and properly addressed. A simulation–optimization approach is proposed to design a system for safe disposal of brine wastes. We use a hydrodynamic model to assess the initial dilution of hypersaline effluent discharged into coastal waters. A regression model is developed to relate the input and output parameters of the simulation model. We then formulate an optimization model to determine the design of a brine disposal system with multiport diffusers in which the regression model replaces the simulation model. The design parameters are the length, diameter and number of ports of the disposal system. Given the parameter uncertainty, a chance-constrained programming model is used. This simulation–optimization framework provides planners with effective tools that meet environmental permitting requirements and restrictions, while achieving cost savings and adequate hydrodynamic performance. A case study demonstrates the applicability of the proposed methodology. •Simulation–optimization framework is presented for a SWRO outfall system design.•A regression model replaces a hydrodynamic model in an MILP formulation.•Design minimizes the cost and is subject to the imposed environmental constraints.•Chance-constrained programming is used to model the stochastic variables.